IMPLEMENTASI PROGRAM PEMBERDAYAAN MASYARAKAT DAERAH OLEH DINAS PETERNAKAN DAN PERIKANAN KABUPATEN GROBOGAN - Alifiati Nurul Aini; Dyah Lituhayu; Rihandoyo Rihandoyo (Journal of Public Policy and Management Review, 2014)
In addressing the impact of the economic crisis that Indonesia, the government implemented a policy to boost the economy of the community programs one of which is in the Local Community Development Programme. Besides PEMD intended to pursue economic recovery. Background Researchers took the title is the number of masyaraka response to the successful implementation of the PEMD program. The problem of this research is conducted and how this mplementasi anything what the obstacle is less successful PEMD program is implemented in the Dinas Peternakan dan Perikanan Grobogan Purwodadi particular districts. This study has the purpose to determine the implementation of the Regional Program for Community Empowerment (PMD) in the District Purwodadi and seek solutions to problems in handling suspected in program implementation (PMD) in the of field Purwodadi Ranch. This study is also expected to provide input to be considered for implementing the PMD program or planning similar programs in the future so that the weaknesses and obstacles can be overcome with good. This research is a descriptive qualitative research. In this study, researchers tried to explain the faktors that affect the implementation of the PMD program. Faktors that influenced them, SDM and attitudes of the target group to be applicable programs. Sources of data used in this study include sourced from interviews, observations, documents, annual activity peternakan & perikanan. The conclusion from this study is that the attitude of the community to support and participate actively in the implementation has been good, although in terms of in-depth understanding of the program is still lacking. Barriers that take place between them is less deep kemasyarakat socialization so that the level of understanding is still kurang..Disarankan dilaksakan as often as possible in order to socialize and review the situation in the field so that breeders know and listen to their complaints. The quality of a good resource that can conduct the start of the planning, implementation, coordination of activities up to, the valuation report preparation dane. The attitude of the target group is indicated by the level of involvement they follow the events that are planned in this PMD program.